Study on the Durability of Recast Nafion/Montmorillonite Composite Membranes in Low Humidification Conditions. (15th September 2010) - Pozio, A.; Cemmi, A.; Mura, F.; Masci, A.; Silva, R. F.
Abstract : Nafion composite membranes were formed from a recasting procedure previously reported by the authors. Montmorillonite (MMT) was used as a filler in the recasting procedure, and dimethylformamide (DMF) was used as the casting solvent. Fuel cell tests performed with the recast membrane showed that at low relative humidity (R.H.) the conductivity of the MMT-containing membranes is 10% higher than that of the MMT-free samples. In order to investigate the durability of such composite perfluorosulfonate membranes, long-term fuel cell experiments have been carried out. Results evidenced a strong effect of low RH on the lifetime of commercial polymer membranes, but the addition of a small silicate amount to the polymeric membrane reduced strongly the membrane degradation.